Leading educational systems and schools in times of disruption and exponential change : a call for courage, commitment and collaboration - Duignan, Patrick (Emerald Publishing Limited, 2020)
Schools and school systems are increasingly impacted by global disruptions and rapid changes that create unprecedented challenges and opportunities for their leaders and educators. School leaders need to prepare students for faster changes than ever before, to learn for jobs that have not yet been created and use pedagogically-informed technologies to transform the ways in which teachers, students. and parents relate and collaborate. Current and future technological transformations provide opportunities for transformative change through the potential for connectivity and networking for educators locally, nationally and internationally. This book provides an analysis of the impact of disruptive environments on education. It closely examines and synthesizes international literature on how educational systems in a number of countries are successfully transforming educational delivery processes to better prepare students for an increasingly disrupted world. This invaluable text will prove indispensable for educational professionals and researchers engaged in informing and transforming policy making, leadership training and development, and quality learning and pedagogy in schools.
Includes index.
Keywords: Educational leadership.; Educational change.; Education -- Leadership.; Organization & management of education.; elektronické knihy; electronic books